"Coxa pedis" today. Issue 2 (June 2016) - Pisani, G.
Highlights: Subtalar joint. Anomalous subtalar pronation syndrome. Flexor digitorum longus transfer pro tibialis posterior tendon. Coxa pedis actor or participant in the functional integration of the lower limb. Anterior knee pain syndrome. Abstract: Coxa pedis is the talocalcaneonavicular joint and is the distal enarthrosis of the lower limb. It is defined coxa because of: (1) the enarthrosic meaning from an anatomical point of view, (2) the analogy to the hip. The stabilising devices are structural, passive and active; the corresponding pathology is the "Coxa pedis destabilising syndrome". During walking, release and stiffening of the foot are related to the opening and closure of the kinetic chain of the coxa pedis: it is mutually reversible, while opening is a passive event, closure is an active one. Considering the importance of the flexor digitorum longus muscle in stabilising the coxa pedis, is it logical transferring it in the tibialis posterior disfunction? During walking, opening and closure of the kinetic chain of the coxa pedis intervene in the opening and closure of the kinetic chain of the entire lower limb. The kinetic chain closes starting from the bottom and moving upwards in the foot–knee–hip progression, and opens starting from the top and moving downwards. Even rotations along the orthogonal plane of the segmental axes of the limb contribute to the closure of the kinetic chain, coxa pedis dysmorphism (cavovalgus foot: false flat foot) can cause, during growth, dysmorphism of the hip (residual anteversion) and of the knee (condyles or tibial tuberosity) instead of the reverse. Issues: subtalar joint; anomalous subtalar pronation syndrome; flexor digitorum longum transfer pro tibialis posterior tendon; coxa pedis actor or participant in the functional integration of the lower limb; anterior knee pain syndrome.